PENDAMPINGAN PENYUSUNAN RENCANA KERJA TAHUNAN SEKOLAH BERKARAKTER - Imam Wahyono; Ahmad Aziz Fanani; Eka Ramiati; Moh. Anas Syamsudin (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to provide assistance in developing the Annual Work Plan for Character-Based Schools at TK Bustanul Falah Kembiritan Genteng, Banyuwangi. This initiative is driven by the need to meet the standards set by the National Education System, which emphasizes effective school management and quality education. The methodology of this service involves a collaborative approach between the PKM team from the Faculty of Tarbiyah at IAI Ibrahimy Genteng Banyuwangi and the stakeholders of the school, including preparation, implementation, and evaluation, which are then packaged in the form of seminars, training sessions, and structured discussions to enhance understanding of preparing the annual work plan in accordance with national education standards. The results of this service have yielded a better understanding of preparing the annual work plan among school principals and teaching staff. Through mentoring and consultation, the school has successfully developed a comprehensive annual work plan tailored to its needs and ready for implementation in the upcoming academic year. As for the sustainability of this service, it emphasizes continuous mentoring and consultation. This support will enable schools to maintain the quality of their annual work plans and effectively implement them in the subsequent academic years, contributing to an overall improvement in school management and educational quality.